THE INFLUENCE OF GREEN MARKETING AND GREEN KNOWLEDGE ACCURACY ON GREEN PRODUCT PURCHASE DECISIONS - Ria Darmasari; Sri Indrastuti; Annisa Mardatillah (Jurnal Al-Iqtishad, 2025)
This study aims to analyze the influence of green marketing and green knowledge accuracy on the decision to purchase green products in Pekanbaru. Using a quantitative method with multiple linear regression analysis, this study involved 100 respondents selected through purposive sampling, with the criteria being residents aged 20–60 years. Primary data were collected through online and offline questionnaires. Partial test results show that green marketing has a positive and significant effect on purchasing decisions. Meanwhile, green knowledge accuracy exerts a much stronger positive effect). Taken together, these two independent variables account for 54.9% of the variance in green product purchase decisions, while the remaining 45.1% is influenced by other factors. These findings underscore the importance of the accuracy of consumers’ objective information in validating environmental claims to encourage consistent consumption decisions regarding green products.